2019
DOI: 10.7717/peerj.7009
|View full text |Cite
|
Sign up to set email alerts
|

On the presence of Dipturus nidarosiensis (Storm, 1881) in the Central Mediterranean area

Abstract: The Norwegian skate Dipturus nidarosiensis (Storm, 1881) has only recently been recorded in the western Mediterranean Sea along the coast of southern Sardinia, off Algeria and the Alboran Sea. The present study confirmed the presence of the species in the Central Mediterranean Sea by identifying morphometric, morphological features and molecular markers. Biological sampling was conducted from 2010 to 2016 on eight specimens collected through commercial landings, offshore observer programmes and scientific surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…The record of a juvenile male confirmed the occurrence of D. nidarosiensis in the Strait of Sicily previously assumed by Massi et al (2017) on the basis of a record of one egg capsule found off Pantelleria Island. The presence of the species supports the role of ecological corridor of the Strait of Sicily in connecting organisms living in the western basin (Cannas et al 2010, Follesa et al 2012, Ramírez-Amaro et al 2017 with those distributed in the Ionian Sea (Carbonara et al 2019). The Strait of Sicily is also considered a biodiversity hotspot for cartilaginous fish in the Mediterranean Sea (Enajjar et al 2015, Bradai et al 2018, Di Lorenzo et al 2018) and this new species record strengthens the importance of this area for the conservation of this vulnerable group, as has already been stated in previous studies (Lauria et al 2015).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The record of a juvenile male confirmed the occurrence of D. nidarosiensis in the Strait of Sicily previously assumed by Massi et al (2017) on the basis of a record of one egg capsule found off Pantelleria Island. The presence of the species supports the role of ecological corridor of the Strait of Sicily in connecting organisms living in the western basin (Cannas et al 2010, Follesa et al 2012, Ramírez-Amaro et al 2017 with those distributed in the Ionian Sea (Carbonara et al 2019). The Strait of Sicily is also considered a biodiversity hotspot for cartilaginous fish in the Mediterranean Sea (Enajjar et al 2015, Bradai et al 2018, Di Lorenzo et al 2018) and this new species record strengthens the importance of this area for the conservation of this vulnerable group, as has already been stated in previous studies (Lauria et al 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Some further records were reported in the same area by Follesa et al (2012). More recently, D. nidarosiensis was found also in the Ionian Sea and the Adriatic Sea (Carbonara et al 2019, Cariani et al 2017, as well as in the Alboran Sea where eight specimens were caught between 2013 and 2016 (Ramírez-Amaro et al…”
Section: Introductionmentioning
confidence: 99%
“…For this nomenclatural issue, it is problematic to consider D. batis as a valid species for the Mediterranean Sea. In this sense, museum collections can provide useful support to solve some of these doubts. Conversely, D. nidarosiensis officially appeared in the Mediterranean faunistic lists only recently (Cannas et al 2010) and subsequently was confirmed by different authors (Follesa et al 2012;Massi et al 2017;Geraci et al 2019;Carbonara et al 2019) particularly for the western and central Mediterranean and the Adriatic Sea. Although, it should be said that further information on its status in the Mediterranean is recommended.…”
Section: Discussionmentioning
confidence: 85%
“…However, its distribution range seems to be enlarged. Indeed, in recent times, some individuals linked to this species have also been caught in the Mediterranean Sea during research expeditions carried out between 2005(Cannas et al 2010Follesa et al 2012;Ramírez-Amaro et al 2017;Carbonara et al 2019;Geraci et al 2019). Although Cannas et al (2010) and Carbonara et al (2019) confirmed the species identification by genetics, Ebert and Stehmann (2013) suggested that individuals caught in the Mediterranean might belong to a smaller morphotype of Dipturus sp.…”
mentioning
confidence: 96%
“…Its dominance can interfere with nutritional cycles, hydrological conditions, and the energy budgets of the plant-soil ecosystem, causing severe economic losses to the agricultural, forestry, and livestock industries (Xu et al, 2006;Kong et al, 2017). Thus, A. adenophora is often used as a model organism to study the possible mechanisms of plant invasion (Datta et al, 2017;Chen et al, 2019;Fang et al, 2019;Poudel et al, 2019;Zhao et al, 2019). The impact of plant soil feedback is of interest to explain the successful exotic invasion of A. adenophora (Niu et al, 2007;Poudel et al, 2019;Zhao et al, 2019).…”
Section: Introductionmentioning
confidence: 99%